Atypical Cutaneous Larva Migrans with Rapid Improvement after Initial Albendazole Therapy: A Case Report - Jilly Selena Pradipta; Marrietta Sugiarti Sadeli (Indonesian Journal of Global Health Research, 2026)
Cutaneous larva migrans (CLM) is a zoonotic helminthiasis caused by the penetration of animal hookworm larvae into the human epidermis and characterized by pruritic serpiginous lesions. This disease is commonly found in tropical and subtropical regions due to exposure to soil or sand contaminated with dog or cat feces. Lesions typically appear on the lower extremities due to direct contact with the soil, but can occur in other locations, posing diagnostic challenges. This study aims to describe the clinical presentation of CLM with unusual lesion locations and highlight the rapid clinical response following initial albendazole therapy. This study used a descriptive observational design with a single case report approach. The study subject was a single patient diagnosed with Cutaneous Larva Migrans with atypical clinical manifestations based on history, physical examination, and the clinical judgment of the treating physician. The patient was selected purposively because of her atypical clinical presentation and interesting therapeutic response to report. The analysis was conducted descriptively, presenting the chronology of the disease course, diagnostic process, response to therapy, and clinical outcomes of the patient. The patient received 400 mg of albendazole once daily for three days and 10 mg of cetirizine once daily. After the first dose of albendazole, the sensation of larval movement and pruritus disappeared. A gradual evaluation revealed a decrease in lesion activity after the second dose, as well as drying of the migration path after the third dose. On the fifth day after therapy, the lesions appeared to be drying out with reduced erythema, indicating a rapid clinical response to anthelmintic therapy. CLM can occur in non-predilection sites such as the trunk and upper extremities, potentially presenting diagnostic challenges. A rapid clinical response to albendazole not only effectively halts larval migration but also has important diagnostic value in atypical presentations.